PEMBANGUNAN PEMBANGKIT TENAGA MIKROHIDRO MODEL BAK (PTMMB) PENGGERAK MESIN PENGGILING TEPUNG - Asep Neris Bachtiar; Trisna Putra; Hariadi (Jurnal Teknik Mesin, 2014)
Researchers in this study will make it back first mover cross flow turbines with larger dimensions and construction of different power system compared with the first year of study. Sedative tub built with brick-concrete construction also functions as a pipe or penstok so rapidly or loses pressure loss is relatively smaller. Thus this generation systems dinamakam micro hydro Power Wagon Model (PTMMB) are used as flour grinding machine mover. PTMMB relatively cheaper investment and implementation in the field relatively quickly, all these advantages into solution in accelerating the spread and development of micro-hydro power plant to the next. By utilizing a head of 1.5 m and a discharge of 100 l / s, projected another plant can generate power of 1,272 kW. From the test results show that the data are encouraging real turbine efficiency is 86.5% greater than the efficiency of plan / assumption is 85%, and thus the quality of early mover Cross Flow turbines are built quite satisfactory and can be proud of. Generating system efficiency measured above 70% which is 76.1% and the productivity of grinding machine at 100% valve opening position is 50 kg / h, which is quite large productivity is very helpful in increasing the production of grinding